The Impact of Performance Appraisal on the Motivational Level of the Employees - Hemani, Amir Ali (2012)
The study aims to highlight the impact of performance appraisal on the motivational level of the employees. It is of great importance for an organization to retain its employees; this can be done by giving them opportunities and appraisals. The agenda of the study is to identify the relationship of compensation, promotion and motivation with performance appraisal. The research aims at the executive and labor class in the Kuala Lumpur, Malaysia. Open-ended structured interviews were conducted, where 10 respondents, 7 from the executive level and 3 from the lowest level of the organizational hierarchy were interviewed, using convenience sampling and narrative analysis method was used for the analysis of the findings. The findings indicated that giving an employee compensation or promotion enables them to be more effective and efficient. Although some interviewees were in view that the performance appraisal is not done on fair basis in their respective organization, and appraisals and promotions were given to those who were connected to the top management. The study reveals the views of employees regarding compensation and performance appraisal and how they want to enhance it for the betterment of the employees as well as for the organization.The research can help the organizations in understanding the requirements of the employees and designing new compensation packages. The study will help employers in understanding their employees in a better manner. Hence, further research might also lead to an improved understanding of the optimal balance between improving the monetary compensation system and promotion opportunities. Although the research was done with very rigid constraints but limitations still exist. The researcher was not able to cover a greater geographical location due to the monetary and time constraints. Never the less the impact of the research despite the limitations is significant. The results indicate the impact of performance appraisals increase the sense of belongingness, increases productivity, loyalty and sense of responsibility in an employee. The research will surely help other researchers to perform and come up with better and improved results in this area.